2020
DOI: 10.1212/wnl.0000000000009991
|View full text |Cite
|
Sign up to set email alerts
|

EEG reactivity testing for prediction of good outcome in patients after cardiac arrest

Abstract: Objective:To determine the additional value of EEG reactivity (EEG-R) testing to EEG background pattern for prediction of good outcome in adult patients after cardiac arrest (CA).Methods:Post-hoc analysis of a prospective cohort study. EEG-R was tested twice a day, using a strict protocol. Good outcome was defined as a Cerebral Performance Category of 1-2 within 6 months. The additional value of EEG-R per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 32 publications
(48 reference statements)
0
17
0
Order By: Relevance
“…34 Since stroke patients had acute spindles loss ipsilaterally to the lesion, but progressively recovering during recovery, it was speculated that spindles are markers of neuronal plasticity. 15,35 The patients' group with spindles also showed a higher prevalence of EEG reactivity, reflecting its association with good outcome after cardiac arrest, 36 and in disorders of consciousness of different etiologies. 37 Since stimulus modality seems crucial to optimize reactivity detection, a standardized protocol, as applied in the CERTA study, is recommended.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…34 Since stroke patients had acute spindles loss ipsilaterally to the lesion, but progressively recovering during recovery, it was speculated that spindles are markers of neuronal plasticity. 15,35 The patients' group with spindles also showed a higher prevalence of EEG reactivity, reflecting its association with good outcome after cardiac arrest, 36 and in disorders of consciousness of different etiologies. 37 Since stimulus modality seems crucial to optimize reactivity detection, a standardized protocol, as applied in the CERTA study, is recommended.…”
Section: Discussionmentioning
confidence: 92%
“…The patients’ group with spindles also showed a higher prevalence of EEG reactivity, reflecting its association with good outcome after cardiac arrest, 36 and in disorders of consciousness of different etiologies 37 . Since stimulus modality seems crucial to optimize reactivity detection, a standardized protocol, as applied in the CERTA study, is recommended 38 …”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort study found that despite epileptiform activity, patients with background continuity ≥50%, absence of epileptiform abnormalities, preserved reactivity on initial and/or repeat EEG, normal background amplitude, and stimulus‐induced rhythmic, periodic, or ictal discharges on subsequent EEG had favorable outcome (CPC 1–3 within 3 months of arrest), whereas burst suppression with identical bursts on EEG were 100% specific in predicting poor outcome 39,40 . Preserved EEG reactivity specifically following cardiac arrest predicted functional independence at 6 months after arrest 41 . The combination of MRI and EEG for determining outcome for patients with post‐anoxic myoclonus found that absence of injury on MRI and preserved EEG background continuity had a positive predictive value of 91% for ability to follow commands and negative predictive value of 99% for coma recovery 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Reactivity Cardiac Arrhythmias -Translational Approach from Pathophysiology to Advanced Care is a significant change in background EEG activity following external stimuli [34]. EEG reactivity following clapping or sternal rubbing indicates good outcomes in PCAS patients [35].…”
Section: Electroencephalogram (Eeg)mentioning
confidence: 99%